The Law and Labour Relations : A Reaction to the Rand Report - Goldenberg, H. Carl (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1969)
After having recalled some basic principles in the field of labour relations, the author, a practician with more than thirty years of experience, deals with subjects such as the right to strike, the need for law and industrial unrest in Canada.